Discovery of Retro-1 Analogs Exhibiting Enhanced Anti-vaccinia Virus Activity - Priyamvada, Lalita; Alabi, Philip; Leon, Andres; Kumar, Amrita; Sambhara, Suryaprakash; Olson, Victoria A.; Sello, Jason K.; Satheshkumar, Panayampalli S. (Frontiers in Microbiology, 2020)
Orthopoxviruses (OPXVs) are an increasing threat to human health due to the growing population of OPXV-naïve individuals post the discontinuation of routine smallpox vaccination. Antiviral drugs that are effective as post-exposure treatments against variola virus (the causative agent of smallpox) or other OPXVs are critical in the event of an OPXV outbreak or exposure. The only FDA approved drug to treat smallpox, TPOXX (ST-246) exerts its antiviral effect by inhibiting extracellular virus (EV) formation thereby preventing cell-cell and long-distance spread. We and others have previously demonstrated that host Golgi-associated retrograde proteins (GARP) play an important role in monkeypox virus and vaccinia virus (VACV) EV formation. Inhibition of the retrograde pathway by small molecules such as Retro-2 has been shown to decrease VACV infection in vitro and to a lesser extent in vivo. To identify more potent inhibitors of the retrograde pathway, we screened a large panel of compounds containing a benzodiazepine scaffold like that of Retro-1, against VACV infection. We found that a subset of these compounds displayed better anti-VACV activity, causing a reduction in EV particle formation and viral spread compared to Retro-1. PA104 emerged as the most potent analog, inhibiting 90% viral spread at 1.3 µM with a high selectivity index. In addition, PA104 strongly inhibited two distinct ST-246-resistant viruses, demonstrating its potential benefit for use in combination therapy with ST-246. These data and further characterizations of the specific protein targets and in vivo efficacy of PA104 may have important implications for the design of effective antivirals against OPXV.